n-3 PUFA and Endothelial Dysfunction: Exploring the Link between Cardiovascular Disease and Risk Reduction - Jirarattanarangsri, Wachira (Asian Health, Science and Technology Reports, 2017)
The loss of normal vascular function has an etiologic role in hypertension, atherogenesis, and vascular reactivity which lead to cardiovascular disease (CVD). Several societies across the world have established dietary recommendations for eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), either from the intake of oily fish or EPA- and DHA-containing supplements that are principally for CVD risk reduction. There is growing evidence that dietary n-3 PUFA may reduce the development of CVD. Because of this, animal and human trials have been investigated for biochemical and metabolic parameters. This article provides information on the benefits of n-3 PUFA by showing the evidence from animal and clinical human studies which suggest that increasing intakes n-3 PUFA may reduce the risk of CVD by improving biomarkers, endothelial function and vascular reactivity.